Overuse of short-acting beta-agonist bronchodilators in COPD during periods of clinical stability. (July 2016) - Fan, Vincent S.; Gylys-Colwell, Ina; Locke, Emily; Sumino, Kaharu; Nguyen, Huong Q.; Thomas, Rachel M.; Magzamen, Sheryl
Abstract: Background: Overuse of short-acting beta-agonists (SABA) is described in asthma, but little is known about overuse of SABA in chronic obstructive pulmonary disease (COPD). Methods: Prospective 3-month cohort study of patients with moderate-to-severe COPD who were provided a portable electronic inhaler sensor to monitor daily SABA use. Subjects wore a pedometer for 3 seven-day periods and were asked to complete a daily diary of symptoms and inhaler use. Overuse was defined as >8 actuations of their SABA per day while clinically stable. Results: Among 32 participants, 15 overused their SABA inhaler at least once (mean 8.6 ± 5.0 puffs/day), and 6 overused their inhaler more than 50% of monitored days. Compared to those with no overuse, overusers had greater dyspnea (modified Medical Research Council Dyspnea Scale: 2.7 vs. 1.9, p = 0.02), were more likely to use home oxygen (67% vs. 29%, p = 0.04), and were more likely to be on maximal inhaled therapy (long-acting beta-agonist, long-acting antimuscarinic agent, and an inhaled steroid: 40% vs. 6%, p = 0.03), and most had completed pulmonary rehabilitation (67% vs. 0%, p < 0.001). However, 27% of overusers of SABA were not on guideline-concordant COPD therapy. Conclusions: Overuse of SABA was common and associated with increased disease severity and symptoms, even though overusers were on more COPD-related inhalers and more had completed pulmonary rehabilitation. More research is needed to understand factors associated with inhaler overuse and how to improve correct inhaler use. Highlights: Overuse of short-acting beta-agonist inhalers was common in moderate to severe COPD. Worse disease severity and increased dyspnea were associated with overuse of SABA. Only half of overusers were on maximal maintenance inhaler therapy for COPD. Interventions to optimizing inhaled therapy should be considered to reduce overuse.